Pengaruh Service Quality dan Online Service-scape Terhadap Keputusan Pembelian Melalui Brand Image (Studi kasus pada Mahasiswa FISIP Undip Pengguna Jasa Transportasi Online Go-Jek) - Benedictus Pascal Kurniawan; Widayanto Widayanto (Jurnal Ilmu Administrasi Bisnis, 2019)
The service of transportation sector is the one of service sector which is needed among many people, the people’s needs of transportation service must be considered. As we know in Indonesia, there is an online transportation service which makes the passengers don’t need to go to the bus stop or the other stations to get the public transportation. Go-Jek is the one of online public transportation which is has the many customers, but there are still many problems in Go-Jek, causing customer to be hesistant to use, as evidenced by the lack of targets and the realization of Go-Jek’s transactions The objective of this research is to investigate the direct impact of Service Quality and Online Servicescape on Purchase Decision and the indirect effect of Service Quality and Online Servicescape on Purchase Decision through Brand image among Go-Jek users in Social and Political Science Faculty of Diponegoro University.  Non Probability sampling with Purposive Sampling and Accidental Sampling is used as methodology research for this research. Samples collected as many as 100 of respondents from S1 students on Social and Political Science Faculty of Diponegoro University who were selected based on consideration. This research uses the Partial Least Square analysis techniques, which are being estimated by the program Warp PLS 3.0. Based on the result of data analysis by using Warp PLS, it indicates that direct impact of the test result on the research modals find out the positive and significant results. Indirect impact of that test result on the research modals are also indicate the positive and significant results. The researcher delivers the suggestion for Go-Jek company to increase service quality by strengthen the Procedure Operational Standard, then make an improvement of the visual quality in Go-Jek application and its website, working with influencer partners that have strong network to be able to exchange customers, and do more promotion to media that it close to potential customers.